Voices from the Field: Combating COVID-19 Pandemic in Nepal - Thapa, Shyam; Thapa, Kulesh B; Bhandari, Robin Jung; Sharma, Ismita; Koirala, Rishav; Kolakshyapati, Shristi; Pandey, Binita; Sharma, Bindu; KC, Elawati; Paudel, Samjhana; et al. (Europasian Journal of Medical Sciences, 2021)
Given the ongoing COVID-19 crisis in Nepal, this section includes some vignettes related to combatting the crisis in Nepal. When the editor-in-chief of this journal invited me to assist, I thought it would be useful to present the experiences of the actual professionals engaged in combating the pandemic in the field. This effort resulted in the collection of seven brief articles/commentaries in this section. These include six articles prepared by six individual authors and one prepared jointly by four coauthors. The experiences shared in these articles are probably just the tip of the iceberg, and there are bound to be more heart-wrenching yet untold stories out there. But these too are no less important in our efforts to fully understanding the context, consequences, and handling of various critical situations as the pandemic has unfolded globally, and in Nepal in particular.